The prevalence of depressive symptoms in women attending antenatal care in primary healthcare clinics in Johannesburg Metro District, South Africa - Malaza, Eliza (My University, 2021)
Background: Perinatal or maternal mental health is a global problem with prevalence ranging from 7 to 40%. The prevalence rate of antenatal depression (AD) is10.7% globally and as high as 20 to 40% in low-and-middle income countries (LMIC) like South Africa. There is currently no routine screening of maternal mental illness in South Africa and there is therefore a paucity of information on prevalence rates and risk factors of maternal mental health conditions, in particular of AD in South Africa, especially in the Gauteng Province. Methods: A convenience sample of 436 pregnant women were recruited from five primary care clinics in the central and south of Johannesburg, while attending routine antenatal visits. All the women completed a socio-demographical questionnaire and the Edinburgh Postnatal Depression Scale (EPDS). Results: The prevalence of AD was 31.3%. In the final multivariate analysis, pregnant women with one or more medical conditions were almost twice as likely to have AD than pregnant women with no medical condition (OR 1.81, 95% CI 1.08-3.02, P-value 0.02). Pregnant women with poor social support were five times more likely to have AD than pregnant women with good social support (OR 5.91, 95% CI 2.25-15.49, P-value 0.002). Employment, level of education, marital status, unplanned pregnancy and intimate partner violence (IPV) were not significantly associated with AD. Conclusion: Although clinical confirmation was not conducted, almost a third of the pregnant women attending antenatal care (ANC) services in primary care clinics were depressed based on the EPDS. The integration of mental health care with existing maternal health services, in-cooperating routine screening of mental illness, referral and treatment for women in the perinatal period will help reduce the adverse maternal and infant outcomes associated with maternal mental illness
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Family Medicine, 2021